Visual Based Sensor Cart Follower For Wheelchair By Using Microcontroller - Rafidi, Nazrin Mohd (Universiti Sains Malaysia, 2017)
For the wheelchair user, it’s difficult to carry their luggage when travelling. It’s difficult for themselves to carry luggage while handling their wheelchair to navigate it smoothly. The vision-based sensor cart follower is the initiative that can lighten the burden for wheelchair user. The method to establish this project by using CMUcam5™, ultrasonic sensor, Arduino MEGA 2560 R3, motor driver, servo motor and driven motor. The CMUcam5™ is the main part in this project since it provides simple vision capabilities to small embedded systems in the form of an intelligent sensor. The ultrasonic sensor is used to prevent the cart from bump any obstacle such as wall and human and keep the cart in certain distance. Motor driver is used to control the movement of the driven motor. The wide angle of servo meter is set from 60° to 120° and important to steer the cart. This visual-based sensor cart follower can help wheelchair user for easier travelling while carrying their luggage.